2004
DOI: 10.1093/jnen/63.9.919
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Denervation in Humans Causes Degeneration of Both Contractile and Excitation-Contraction Coupling Apparatus, Which Is Reversible by Functional Electrical Stimulation (FES): A Role for Myofiber Regeneration?

Abstract: Over the last 30 years there has been considerable interest in the use of functional electrical stimulation (FES) to restore movement to the limbs of paralyzed patients. Spinal cord injury causes a rapid loss in both muscle mass and contractile force. The atrophy is especially severe when the injury involves lower motoneurons because many months after spinal cord injury, atrophy is complicated by fibrosis and fat substitution. In this study we describe the effects of long-term lower motoneuron denervation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
239
1
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(262 citation statements)
references
References 33 publications
8
239
1
14
Order By: Relevance
“…A variable percentage of fibers were instead severely atrophic (4-23%, Table 5, column C) and resemble those found in patients that lost their peripheral nerve endings. 7 Some peculiar features allowed us to clearly distinguish large striated fibers in our patients from fibers of controls. 25 The myofibrillar apparatus, while quite well preserved, is in general less ordered than in normal muscle (Figure 5c, black arrows).…”
Section: Force Measurementmentioning
confidence: 85%
See 2 more Smart Citations
“…A variable percentage of fibers were instead severely atrophic (4-23%, Table 5, column C) and resemble those found in patients that lost their peripheral nerve endings. 7 Some peculiar features allowed us to clearly distinguish large striated fibers in our patients from fibers of controls. 25 The myofibrillar apparatus, while quite well preserved, is in general less ordered than in normal muscle (Figure 5c, black arrows).…”
Section: Force Measurementmentioning
confidence: 85%
“…Our observations showed that: (i) human skeletal muscles survive longer (in years) than generally accepted on the basis of experiments in rodents; [4][5][6] (ii) recovery to clinically significant muscle size and function occurs in mid-term (3-5 years) lower motor neuron SCI subjects; 7,8 but (iii) starting FES within the first year post-lesion results in a better recovery of muscle function than when started many years after SCI. 9 To date, however, there is little knowledge about the longterm progression of muscle atrophy in upper motor neuron lesion (UML) patients .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, various muscles innervated from the lesion epicenter have been unresponsive to electrical stimulation of their peripheral nerves, consistent with complete muscle denervation. [14][15][16][17][18] Other studies have shown signs of partial denervation (low motor unit counts, positive sharp waves, small amplitude compound muscle action potentials, muscle weakness that exceeds that expected from disuse atrophy, atrophied and angular muscle fibers), including indications of intramuscular motor axon sprouting, an important compensatory mechanism for recovery of muscle innervation after death of some motoneurons in a motor pool (large polyphasic motor unit potentials, stronger than usual motor unit forces, increased motor unit fiber density, increased jitter in re-innervated muscle fibers). 12,[19][20][21][22][23] In this study, we address an important and often overlooked aspect of SCI-the effect of injury on the lesioned spinal cord segment and denervation of skeletal muscle as a contributor to muscular weakness.…”
Section: Introductionmentioning
confidence: 99%
“…7 Muscle biopsies from patients with spinal cord injury lasting from 9 months to 19 years also contained immature fibers, which were interpreted as regenerative in nature. 8,11,14,15 These fibers had a central nucleus and a thin cytoplasmic rim containing a few myofilaments, and expressed the embryonic isoform of the myosin heavy chain molecule (MHCemb). They represented about 1% of the total myofiber population in these muscle biopsies.…”
mentioning
confidence: 99%